Training-induced changes in aerobic and anaerobic capacity and resting hormonal status in blood in elite male and female speed skaters - Obminski, Z.; Litwiniuk, A.; Borkowski, L.; Ladyga, M.; Szczepanska, B. (LASE Journal of Sport Science, 2014)
To date, there is only one published study with the use standardized ergometry exercise tests regarding effect of long lasting training period on a change of physical fitness among international level male and female speed skaters (van Ingen Schenau JG, 1992). This study showed high level initial performance and lack of its improvements despite trainings. That phenomenon might be resulted in inadequate training modalities, accumulation of fatigue or simply such high initial fitness, that it was impossible to improve it. Our study was aimed to examine the responses of several biomechanical and physiological parameters to preparatory training period (4 months) with incising predominance of strength - velocity exercises over time course. The results showed minor, non-significant improvements of some parameters of anaerobic and aerobic capacity in the males. In females there was no change in aerobic capacity, and those in anaerobic one were lower than in males . After the period in both sexes resting blood cortisol was elevated and testosterone-to-cortisol ratio, was declined, that suggest shift of protein metabolism toward catabolism. We suspect that among females their adverse hormonal status may have been responsible for, general lower expected training effects.